Study and design of topologies and components for high power density DC-DC converters - Calabrese, Giacomo (Premio Tesi di Dottorato, 2016)
Size reduction of low power electronic DC-DC converters is a topic of major interest for power electronics which requires the study and design of circuits and components working under redefined requirements. For this purpose, novel circuital topologies provide advantages in terms of power density increment, especially where a single chip design is feasible. These concepts have been applied to design and implement an integrated high step-down multiphase buck converter and to study the miniaturization of a stackable fiflyback architecture. Particular attention has been dedicated to power inductors, focusing on the modeling and measurement of magnetic materials' hysteresis and core losses.